If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + t = 14 Solving 6 + t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + t = 14 + -6 Combine like terms: 6 + -6 = 0 0 + t = 14 + -6 t = 14 + -6 Combine like terms: 14 + -6 = 8 t = 8 Simplifying t = 8
| 7-2a=7 | | m+17=33 | | 2x+3x=-62-28 | | 10x^2+9x+6=0 | | 28-16= | | -10x-6x=8-9x | | -6=k-6 | | 2x^2-22x-120=0 | | 10x+20(95-x)=1400 | | -5n^2+6n-6=0 | | 3*6-2= | | r/3=10 | | -5=k+5 | | -2m^2+4m-2=0 | | 14x+12y=54000 | | 42v^2+v=30 | | 6(5x+9)=30x+54 | | 14x+12y=54 | | x-24=x+24 | | 8+7x=32 | | 0.08(y-5)+0.16y=0.04y-1.5 | | P=2x+y | | p-1=sp+3p-8 | | t+11=6 | | 4p^2-p-3=-6 | | (3m^2+7m+2)(4m+6)= | | 3x-x=27-19 | | 6n+3n=16+20 | | 5+2(x-3)=2(5-4(x+2)) | | 27.8+(-49.53)= | | 0.5x+0.45(50)=42.5 | | 1700+.05x=1950 |